Effects of organic fertilization from wet olive pomace on emmer wheat (Triticum dicoccum Shrank) grain yield and composition. (November 2021) - Lacolla, Giovanni; Rinaldi, Michele; Savino, Michele; Russo, Mario; Caranfa, Davide; Cucci, Giovanna
Abstract: In a circular economy framework, the evaluation of waste by-product use as fertilizer is essential to promote sustainable agriculture. Olive oil wet pomace can be a valuable alternative as organic fertilizer on cereal crops. Aim of the study is to evaluate the effects of organic (with olive oil waste pomace) fertilization, on grain yield, protein and polyphenol content of emmer wheat grown in Southern Italy. Different amounts, time and amount of application of organic fertilizer were compared to a traditional mineral fertilizer treatment. The chemical analysis, mainly grain protein content and phenolic acids contents, were carried out on the hulled seeds. Agronomic traits showed that the application of olive wet pomace at 140 Mg ha −1 in the first year and 70 Mg ha −1 in the second year, gave the best grain yield than an annual amount application of 70 Mg ha −1 . No difference between organic and mineral fertilization was observed when the latter was carried 1 or 2 years before, and the organic fertilization increased grain protein content respect to mineral one. Polyphenol content was not significantly affected by fertilization treatments, while ferulic acid in the emmer grain recently fertilized with wet pomace showed a higher content than emmer fertilized 2–3 years before. Graphical abstract: Image 1 Highlights: Application of olive wet pomace at 140 in the 1st and 70 Mg ha −1 in the 2 nd year, gave the best emmer grain yield. No difference between organic and mineral fertilization when the latter was carried 1 or 2 years before. The organic fertilization increased grain protein content respect to mineral one. Polyphenol content was not clearly affected by fertilization treatments. Ferulic acid showed higher content in the emmer fertilized with wet pomace recently than earlier.